PERAN BUDAYA DAN AKULTURASI DALAM INFORMATION SHARING DALAM ASPEK AKUNTANSI KEPERILAKUAN - DODDY PRIMAYUDIA (Faculty of Economics and Business, Jenderal Soedirman University, 2019)
Information is a crucial point in order to helps managers in decision making. Employees who acts as an agent on agency theory, will gladly report their achievement to their principal. On the other hand, employees tend to cover their faults, especially if the company’s targets are not achieved. There are many factors influencing the employees’ willingness to share the informations, prior to their faults or errors, and two of them are culture and the existence of the supervisor. This research uses experimental method and 2 × 2 factorial design to test the hypotheses. The sample in this research are low-acculturated Tionghoa (TAR) and high-acculturated Tionghoa (TAR). After the research is done, it is come to conclusion that; employees’ cultural background and acculturation did affect their willingness in information sharing. This research also concluded that the presence of supervisor did not affect employees’ willingness in information sharing prior to their faults and errors.